1997
DOI: 10.1016/s0928-8244(97)00027-8
|View full text |Cite
|
Sign up to set email alerts
|

Augmented inhibition of growth of Candida albicans by neutrophils in the presence of lactoferrin

Abstract: The combined inhibitory effects of neutrophils and lactoferrins on the growth of Candida albicans were examined. Murine or human neutrophils partially inhibited growth of C. albicans when cultured with C. albicans in vitro. The growth inhibition was augmented by a combination of neutrophils and more than 30 microg/ml of bovine lactoferrin or 1 microg/ml of human lactoferrin, concentrations less than 1/10-1/200 their inhibiting concentrations when used alone. The inhibition of C. albicans was also enhanced by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Numerous studies in the past have examined aspects of the neutrophil-pathogen response, investigating various microorganisms, including C. albicans (8,23,29,32,35). Recent studies have also investigated the global transcriptional responses of C. albicans to phagocytes/neutrophils, monocytes, and macrophages (10,21,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in the past have examined aspects of the neutrophil-pathogen response, investigating various microorganisms, including C. albicans (8,23,29,32,35). Recent studies have also investigated the global transcriptional responses of C. albicans to phagocytes/neutrophils, monocytes, and macrophages (10,21,33).…”
Section: Discussionmentioning
confidence: 99%
“…Components potentially involved in killing include lactoferrin, which is secreted in the PMN fractions. Several previous studies have demonstrated the candidacidal properties of lactoferrin (29,39,41). The only gene representing the neutrophil granule proteins, which was significantly upregulated, was the protease urokinase-type plasminogen activator (i.e., PLAU) (13).…”
Section: Discussionmentioning
confidence: 99%
“…albicans germ tube assay. A crystal violet-based germ tube assay was used to measure germination as previously described (1,31,46). C. albicans strain CHN1 was grown in sabouraud dextrose broth (SDB) at 22°C (room temperature) while shaking for 48 to 72 h. Samples were washed in 1ϫ phosphatebuffered saline (PBS) and resuspended in 100% fetal bovine serum (FBS) to give a final concentration of 10 6 yeast cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Transferrin [8,23], lactoferrin [1,7,16] and calprotectin [1,19,24] are well known antifungal substances associated with innate immunity in humans and animals. Transferrin and lactoferrin, which are present in blood and in mucus secretions, respectively, are chelating proteins sequestering iron while calprotecitn, which is present in neutrophil, is a chelating protein for calcium and zinc.…”
mentioning
confidence: 99%